2024
DOI: 10.1101/2024.02.17.579363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Gehan test identifies life-extending compounds overlooked by the log-rank test in the NIA Interventions Testing Program: Metformin, Enalapril, caffeic acid phenethyl ester, green tea extract, and 17-dimethylaminoethylamino-17-demethoxygeldanamycin hydrochloride

Nisi Jiang,
Jonathan Gelfond,
Qianqian Liu
et al.

Abstract: The National Institute on Aging Interventions Testing Program (ITP) has so far identified 12 compounds that extend the lifespan of genetically heterogeneous mice using the log-rank test. However, the log-rank test is relatively insensitive to any compound that does not uniformly reduce mortality across the lifespan. This test may thus miss compounds that only reduce mortality before midlife, for example, a plausible outcome if a compound only mitigates risk factors before midlife or if its efficacy is reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Many aging interventions exert varying impacts at different life stages. For example, in an earlier analysis of data from the Interventions Testing Program (ITP), we found that many tested interventions do not adhere to the PH assumption, challenging the applicability of the log-rank test in these contexts 6 . For these interventions, we utilized the Gehan test, more robust to the PH consistency requirement and more sensitive to the effects during early adulthood.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many aging interventions exert varying impacts at different life stages. For example, in an earlier analysis of data from the Interventions Testing Program (ITP), we found that many tested interventions do not adhere to the PH assumption, challenging the applicability of the log-rank test in these contexts 6 . For these interventions, we utilized the Gehan test, more robust to the PH consistency requirement and more sensitive to the effects during early adulthood.…”
Section: Introductionmentioning
confidence: 97%
“…For these interventions, we utilized the Gehan test, more robust to the PH consistency requirement and more sensitive to the effects during early adulthood. Notably, it identified five new life-extending candidates 6 . Despite its strengths, the Gehan test has its own drawback: a diminished sensitivity to effects manifesting at later life stages 7 .…”
Section: Introductionmentioning
confidence: 99%